Impact of Liver Inflammation on Bile Acid Side Chain Shortening and Amidation - Marta Alonso-Peña; Ricardo Espinosa-Escudero; Heike M. Hermanns; Oscar Briz; Jose M. Herranz; Carmen Garcia-Ruiz; Jose C. Fernandez-Checa; Javier Juamperez; Matias Avila; Josepmaria Argemi; Ramon Bataller; Javier Crespo; et al. (Cells, 2022)
Bile acid (BA) synthesis from cholesterol by hepatocytes is inhibited by inflammatory cytokines. Whether liver inflammation also affects BA side chain shortening and conjugation was investigated. In human liver cell lines (IHH, HepG2, and HepaRG), agonists of nuclear receptors including the farnesoid X receptor (FXR), liver X receptor (LXR), and peroxisome proliferator-activated receptors (PPARs) did not affect the expression of BA-related peroxisomal enzymes. In contrast, hepatocyte nuclear factor 4α (HNF4α) inhibition down-regulated acyl-CoA oxidase 2 (ACOX2). ACOX2 was repressed by fibroblast growth factor 19 (FGF19), which was prevented by extracellular signal-regulated kinase (ERK) pathway inhibition. These changes were paralleled by altered BA synthesis (HPLC-MS/MS). Cytokines able to down-regulate cholesterol-7α-hydroxylase (CYP7A1) had little effect on peroxisomal enzymes involved in BA synthesis except for ACOX2 and bile acid-CoA:amino acid N-acyltransferase (BAAT), which were down-regulated, mainly by oncostatin M (OSM). This effect was prevented by Janus kinase (JAK) inhibition, which restored BA side chain shortening and conjugation. The binding of OSM to the extracellular matrix accounted for a persistent effect after culture medium replacement. In silico analysis of four databases (n = 201) and a validation cohort (n = 90) revealed an inverse relationship between liver inflammation and ACOX2/BAAT expression which was associated with changes in HNF4α levels. In conclusion, BA side chain shortening and conjugation are inhibited by inflammatory effectors. However, other mechanisms involved in BA homeostasis counterbalance any significant impact on the serum BA profile.